(untitled) (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
The purpose of this article is to establish and calculate unearned premium reserves, unexpected risk reserves and extraordinary risk reserves based on non-life insurance premiums. Non-life insurance companies calculate unearned premium reserves based on premiums received to protect policyholders against each valid insurance policy they assume as liabilities, and the unexpected risk reserve is established as a result of an adequacy test that demonstrates that adequate reserves are calculated based on future losses and expenses. By applying a liability adequacy test (LAT) based on the 12-month historical performance of a non-life insurance company, the adequacy of the unexpected risk reserve for 2 different indicators was simulated. The equalization reserve created for other extraordinary risks in non-life insurance is determined according to each country’s own catastrophic risk. Keywords: unearned premium reserve (UPR), 1/365 (pro-rata) method, unexpected risk reserve (URR), equalization reserve, liabilities adequacy test (LAT), catastrophic risks